Pelatihan Administrasi Bagi Aparat Dusun Sarsangg - Reivandy Christal Joenso; Anton Topan (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
The problem faced by Hamlet Sarsangg, Tanah Miring District, Merauke Regency is the difficulty in managing administration because Hamlet Sarsangg is still attached to Kampung Yasa Mulya which is quite far away and public transportation is not available. Therefore, counseling and administrative training activities were carried out using the counseling and training method which consisted of 3 stages, namely counseling on the importance of administrative activities, administrative training using Microsoft Office software, and archiving training. The people who were involved in this service activity were the Sarsang Hamlet Bamuskam, the Head of the RT of Sarsangg Hamlet, and the Head of the RW of Sarsangg Hamlet. The expected result of this community service activity is that Sarsangg Hamlet officials have the ability in administrative activities and administrative filing. It is hoped that the acquired skills will become material for consideration for the Regional Government of Merauke Regency to make Sarsangg Hamlet a definitive Sarsangg Village, especially in terms of human resources who have good administrative skills. Administrative extension and training activities are expected to help the people of Sarsangg Hamlet in administrative matters and improve the quality of human resources in Sarsangg Hamlet.